Rotation induced flow suppression around two tandem circular cylinders at low Reynolds number. (5th June 2017) - Chatterjee, Dipankar; Gupta, Krishan; Kumar, Virendra; Varghese, Sachin Abraham
Abstract: The rotation to a bluff object is known to have a stabilizing effect on the fluid dynamic transport around the body. An unsteady periodic flow can be degenerated into a steady flow pattern depending on the rate of rotation imparted to the body. On the other hand, multiple bodies placed in tandem arrangement with respect to an incoming flow can cause destabilization to the flow as a result of the complicated wake interaction between the bodies. Accordingly, the spacing between the bodies and the rate of rotation have significant impact on the overall fluid dynamic transport around them. The present work aims to understand how these two competing factors are actually influencing the fluidic transport across a pair of identical rotating circular cylinders kept in tandem arrangement in an unconfined medium. The cylinders are subjected to a uniform free stream flow and the gaps between the cylinders are varied as 0.2, 0.7, 1.5 and 3.0. Both the cylinders are made to rotate in the clockwise sense. The Reynolds number based on the free stream flow is taken as 100. A two-dimensional finite volume based transient computation is performed for a range of dimensionless rotational speeds of the cylinders (0 ≤ Ω ≤ 2.75). The results show that the shedding phenomena can be observed up to a critical rate of rotation (Ωcr ) depending on the gap spacing. Beyond Ωcr, the flow becomes stabilized and finally completely steady as Ω increases further. Increasing the gap initially causes a slight decrease in the critical rotational speed, however, it increases at a rapid rate for larger gap spacing.